INTEGRASI ISLAMIC HUMAN RESOURCE MANAGEMENT DAN ETIKA KERJA ISLAM DALAM MENINGKATKAN KINERJA KARYAWAN: PENDEKATAN MAQASHID SYARIAH - Yusnita Yusnita; Fitri Yani (Smart Education, 2026)
Abstract: The growth of Sharia-based organizations necessitates a human resource management system that is not only productivity-oriented but also capable of integrating values ​​of ethics, justice, well-being, and sustainability. This study aims to analyze and develop an integrative model of the relationships among Islamic Human Resource Management (IHRM), Islamic Work Ethics (IWE), Employee Performance (EP), and Organizational Sustainability (OS) from the perspective of *Maqashid Sharia* (the objectives of Sharia). A quantitative approach with an explanatory research design was employed, utilizing a five-point Likert scale questionnaire administered to employees of Sharia-based organizations or institutions. The research model positions IHRM as the exogenous variable, IWE as the mediating variable, Employee Performance as the endogenous variable, and Organizational Sustainability as the final outcome. The analysis of relationships between variables was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM), involving the evaluation of measurement and structural models as well as mediation effect testing. The conceptual framework demonstrates that IHRM implementation—encompassing Islamic-based recruitment and selection, training and development, performance appraisal, fair remuneration and compensation, and spiritual development—has the potential to strengthen Islamic work ethics. The internalization of values ​​such as trustworthiness (*amanah*), honesty, responsibility, hard work, discipline, justice, cooperation, and an orientation toward the common good (*maslahah*) serves as a mechanism that drives improved employee performance and supports organizational sustainability. The *Maqashid Sharia* perspective broadens the orientation of human resource management from mere economic achievement toward human development, well-being, justice, and long-term public interest. Keywords: Islamic Human Resource Management; Islamic Work Ethics; Organizational Sustainability Abstrak: Perkembangan organisasi berbasis syariah membutuhkan sistem pengelolaan sumber daya manusia yang tidak hanya berorientasi pada produktivitas, tetapi juga mampu mengintegrasikan nilai etika, keadilan, kesejahteraan, dan keberlanjutan. Penelitian ini bertujuan menganalisis dan mengembangkan model integratif hubungan Islamic Human Resource Management (IHRM), Islamic Work Ethics (IWE), Employee Performance (EP), dan Organizational Sustainability (OS) dalam perspektif Maqashid Syariah. Penelitian menggunakan pendekatan kuantitatif dengan desain explanatory research, sedangkan pengumpulan data dirancang melalui kuesioner menggunakan skala Likert lima poin pada karyawan organisasi atau lembaga berbasis syariah. Model penelitian menempatkan IHRM sebagai variabel eksogen, IWE sebagai variabel mediasi, Employee Performance sebagai variabel endogen, dan Organizational Sustainability sebagai outcome akhir. Analisis hubungan antarvariabel dirancang menggunakan Partial Least Squares Structural Equation Modeling (PLS-SEM) melalui evaluasi measurement model, structural model, dan pengujian efek mediasi. Kerangka konseptual menunjukkan bahwa implementasi IHRM melalui rekrutmen dan seleksi berbasis Islam, pelatihan dan pengembangan, penilaian kinerja, remunerasi dan kompensasi yang adil, serta pengembangan spiritual berpotensi memperkuat etika kerja Islam. Internalisasi nilai amanah, kejujuran, tanggung jawab, kerja keras, disiplin, keadilan, kerja sama, dan orientasi kemaslahatan selanjutnya diposisikan sebagai mekanisme yang mendorong peningkatan kinerja karyawan dan mendukung keberlanjutan organisasi. Perspektif Maqashid Syariah memperluas orientasi pengelolaan sumber daya manusia dari sekadar pencapaian ekonomi menuju pengembangan manusia, kesejahteraan, keadilan, dan kemaslahatan jangka panjang. Kata Kunci: Islamic Human Resource Management; Islamic Work Ethics; Organizational Sustainability